Monitoring technology for the efficiency of utilisation and development of the export-import potential of economic entities of the state sector - Liudmyla Malyarets; Oleksii Budarin (University Economic Bulletin, 2024)
This study aimed to identify approaches for assessing the efficiency of utilisation and development of the export-import potential of Ukrainian state-owned enterprises, considering the influence of external and internal factors. Additionally, a comprehensive monitoring system was developed to enhance competitiveness and facilitate strategic planning in their operations. The research methodology was based on the application of quantitative and qualitative methods for analysing economic performance indicators of state-owned enterprises and their external trade potential. A SWOT analysis was conducted on the proposed multi-level monitoring system, which was also assessed through a change management model. The study contextualised the strategic planning of the export-import potential of economic entities in the state sector of the economy. The impact of political, economic, social, technological, environmental, and legal factors on the export import activities of state-owned enterprises was identified, with particular emphasis on the challenges arising from fullscale military aggression. A 17-stage monitoring technology for export import potential has been proposed, integrating quantitative and qualitative analysis methods, including profitability assessment, competitiveness evaluation, and import and export dependency analysis. The implementation of the proposed technology has been examined through the lens of Kurt Lewin's transformational model, which entails a phased adaptation to changes and the consolidation of new approaches in strategic management. The findings of the contextual study also confirm the significance of international support, market diversification, and innovation in restoring export-import potential. The study focused on the public sector of the economy and the need to adapt monitoring tools to the specific conditions of enterprises. The conclusions drawn may serve as a basis for developing strategies to support state-owned enterprises, enhance their competitiveness, and ensure sustainable development amid external and internal challenges
Keywords: 330; contextual analysis; strategic planning; competitiveness; foreign trade activity; trade balance